Factors Predicting Caregiver Contributions to Self-care in Patients with Heart Failure - Jataisong, Porntip; Poungkaew, Autchariya; Sriyuktasuth, Aurawamon; Chirakarnjanakorn, Srisakul (Journal of Thailand Nursing and Midwifery Council, 2024)
Introduction Caregivers play an important role in contributing to self-care in patients with heart failure (HF). To date, knowledge regarding factors associated with caregiver contributions to self-care remains limited, particularly in Thai patients with HF. Objective This study aimed to 1) describe caregiver contributions to self-care, and 2) examine factors predicting caregiver contributions (self-care maintenance, symptom perception, self-care management) of patients with HF. Design This correlational predictive study was guided by a situation-specific theory of caregiver contributions to heart failure self-care. Methodology The study included 128 caregivers of patients with heart failure, who were purposively selected based on the following inclusion criteria: aged at least 18 years, unpaid for their caregiving tasks, and living with the patients who attended the heart failure clinic and general internal medicine clinic at an outpatient department of a super-tertiary hospital from April to August 2023. Data collection was conducted using questionnaires and record forms, and the data were analyzed using descriptive statistics, simple linear regression, and multiple linear regression. Results The majority of the participants were female (75.78%), with an average age of 46.10 years (SD = 13.74). Caregiver contributions (CC) to symptom perception and self-care maintenance were found to be adequate, with means of 73.38 (SD = 14.83) and 72.72 (SD = 13.75), respectively. In contrast, self-care management was deemed inadequate, with a mean of 68.83 (SD = 16.56). Multiple linear regression analysis revealed that health perception and self-efficacy together predicted CC for symptom perception, explaining 35.20% of the variance. Health perception, self-efficacy, and positive aspects of caregiving together predicted CC to self-care maintenance, explaining 31.50% of variance. Self-efficacy and comorbidities in patients together predicted CC to self-care management, explaining 21.20% of variance. While the status of caregivers to patients was not a statistically significant predictor of all three dimensions of CC to self-care in the patients with HF in this study. Recommendation The results of this study can be utilized to develop specific programs aimed at enhancing caregiver contributions to the self-care of patients with HF, particularly in promoting self-efficacy, positive aspects of caregiving, caregivers’ health perception, and managing the comorbidities of the patients.